Characterisation of manganese toxicity tolerance in Arabis paniculata - Tang, Ting (Plant Divers, 2020)
Manganese (Mn) contamination limits the production and quality of crops, and affects human health by disrupting the food chain. Arabis paniculata is a pioneer species of Brassicaceae found in mining areas, and has the ability to accumulate heavy metals. However, little is known about the genetic mechanisms of Mn tolerance in A. paniculata. In this study, we found that Mn tolerance and ability to accumulate Mn were higher in A. paniculata than in Arabidopsis thaliana. The mechanisms underlying the response and recovery of A. paniculata to Mn toxicity were further investigated using transcriptome analysis. A total of 69,862,281 base pair clean reads were assembled into 61,627 high-quality unigenes, of which 41,591 (67.5%) and 39,297 (63.8%) were aligned in the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO), respectively. In response to Mn toxicity, genes were expressed in twelve distinct patterns, which can be divided into four general categories: initial, stable, dose-dependent, and lineage. Genes that were differentially expressed during Mn response and recovery belong to several dominant KEGG pathways. An early response to Mn toxicity in A. paniculata includes the upregulation of genes involved in glutathione metabolism. ATP-binding cassette (ABC) transporter proteins were up-regulated during the entire response phase, and genes involved in glycerophospholipid metabolism were up-regulated during the late phase of the Mn response. Genes in the phenylpropanoid pathway were differentially expressed in the repair process after Mn treatment. These findings reveal ideal material and genetic resources for phytoremediation in Mn-contaminated areas and highlight new knowledge and theoretical perspectives on the mechanisms of Mn tolerance.